A new approach for characterizing internal stress of fresh concrete during thermal treatment period - Yu Xiang; Jionghuang He; Guangcheng Long; Youjun Xie; Jilin Wang (Case Studies in Construction Materials, 2024)
Addressing the scarcity of research on the residual expansion deformation of steam-cured concrete and its underlying factors, this study introduces a testing apparatus to characterize the internal stress in fresh concrete during the thermal treatment. It explores the impact of water-to-cement ratio (w/c) and paste-to-aggregate ratio (p/a) on internal stress and elucidates the developmental patterns of internal stress in concrete throughout the thermal treatment phase. The key findings are as follows: (i) During the thermal treatment, the internal stress in concrete under constraint is predominantly compressive, exhibiting a rapid increase in the heating stage, followed by a gradual decline in the constant temperature treatment stage, and a continued decrease with a decelerating trend during the cooling stage. (ii) Both w/c and p/c significantly influence internal stress in concrete, and this stress can be enhanced by reducing the initial free water content and augmenting the initial structural strength of the concrete. This paper serves as a valuable foundation and reference for further investigations into the residual expansion deformation of steam-cured concrete.